Bakheel aur mukhtalif kahaniyan - Shahab, Skiekh (Children Publication Karachi, 2012)
This book likely contains stories centered around a miserly character and their experiences. The narratives might explore the negative consequences of greed, selfishness, and the inability to share. Through these tales, readers can learn valuable lessons about the importance of generosity, contentment, and the true meaning of wealth.